Performance Management and the COVID-19 Pandemic: Framework for an Agile Performance Management System for the South African Higher Education Institution - Kanyangale, MacDonald Isaac; Chikandiwa, Christopher Tarisayi (Acta Universitatis Danubius. Œconomica, 2022)
The main objective of this article is to shed some light on one of the burning questions in the South African university on how to manage people's performance in disruptive times. There is a shortage of scholarly work exploring PM during the COVID-19 in the university. Most of the extant studies examined PM before universities were forced to use Remote Emergency Teaching and Learning (RETL), the remote and hybrid work model. This article attempts to achieve its main objective by first re-examining the weaknesses of the traditional PM systems during disruptive times and developing an innovative performance management system to bridge the gap. An Agile performance management system framework for South African Higher Education Institution (HEI) was developed in light of the pitfalls of the PM systems and other relevant literature. The proposed Agile, Continuous Performance Management framework calls for an agile mind-set and the development of new competencies, which include manager-as-coach and compassionate leadership. This article is valuable as it does not only fill this gap by bringing together the pitfalls of PM during the COVID-19 in a South African HEI. It also calls for strategic change and reconceptualisation of PM to provide a strategic way forward.